Teacher perspectives on value creation and learning in South African eco-schools: an evaluative review of teacher support processes in an eco-school professional learning community - Khan, Anisa (Rhodes University, Faculty of Education, Department of Education, 2018)
The study is framed within the broader policy context of teacher professional development and the Department of Basic Education (DBE) and Department of Higher Education (DHET) strategy to support the development of Professional Learning Communities. Teacher Education and Development initiatives in South Africa face multiple challenges, with the Integrated Strategic Planning Framework for Teacher Education in South Africa: 2011-2025 (ISFPTED) (South Africa, DBE, 2011) providing guidance on priority interventions to address these, including guidance on continuous teacher professional development through teacher education support in professional learning communities. The Eco-Schools programme has, over its decade-long history, provided support to teachers in schools registered as Eco-Schools. The value created by the diverse support practices is not well known or understood. The study aimed to shed light on the support teachers in the Eco-Schools programme value and how this contributes to environmental learning and practice. Working with Wenger's Communities of Practice theory (Wenger, 1998) as a conceptual framework and lens, the study set out to describe and explore the processes of teacher learning amongst a sample of teachers supported to function as a professional learning community within the Eco-Schools programme. The findings and recommendations made are in relation to the research goals which are to explore and describe the value being created by the patterns of teacher support in an Eco-Schools node/cluster. To this end, the evaluative study generated evidence in relation to what teachers derive value from through the support they receive; and assessed evidence on how teaching, learning, and practice are developing through participation in the Eco-Schools Professional Learning Community examined. The study was conducted in 2 phases, the first as a survey of the patterns of support in Eco-School clusters/ nodes. The descriptions enabled a mapping of the patterns of support in the "coordinator supported model" of Eco-Schools to understand how the coordinator supported model of Eco-Schools enables teacher collaboration and supports the development of an environment and sustainability community of practice between teachers from across the cluster/ node. The second part of the study explored teacher's perspectives of value derived from participation in an expanded model of Eco-Schools support, using an appreciative inquiry methodology to extract teacher narrations of value creation and meaning-making. In relation to goal one, the main findings indicate that the patterns of support enabled teachers to develop confidence and skills for action taking and responding to local socio-economic and environmental challenges. The data also reflected local partnerships with other environmental knowledge organisations, thus adding value to the programme through an expanded network of environmental practice and provision of additional resources. In relation to goal 2 of the study, teachers experienced Eco-School practices as personally meaningful and connected to their identity. Teachers expressed value in the training they had received through the Fundisa for Change programme which deepened their understanding of the implementation requirements of the Curriculum and Assessment Policy Statements (CAPS) and helped to connect knowledge concepts in the curriculum with sustainability practices implemented as part of the Eco-Schools framework. In relation to goal 3, teachers gained confidence in "Teaching Biodiversity" through the Fundisa for Change training. Teachers were better able to understand the Specific Aims of the Biodiversity curriculum (CAPS) and to adapt their teaching methods to support the CAPS content and assessment requirements. Teacher portfolios also showed evidence of teachers developing skills in analysis of learner performance and an awareness of the need to adjust their teaching and assessment strategies to address "gaps" in learner understanding.
Keywords: Teachers -- In-service training -- South Africa; Environmental education -- Study and teaching -- South Africa; Continuing education; Teachers -- Attitudes; Communities of practice -- South Africa; Integrated Strategic Planning Framework for Teacher Education; Eco-schools